KEANEKARAGAMAN ARTHROPODA PADA TANAMAN JAGUNG TRANSGENIK - Daniel T Tambunan; Darma Bakti; Fatimah Zahara (Universitas Sumatera Utara, 2013)
Biodiversity of arhtropoda on the transgenic corn. The objective of this research was to studyinfluence of variety introduction of varieties arthropoda in transgenic corn. This research was takenat Balai Benih Tanaman Palawija, Kelurahan Tanjung Selamet, Medan start on March 2012 untilMay 2012. This research used 3 design traps of insect (pitfall trap, sweep net, sticky trap),andrepeated three times. The result of research showed that the highest insect value was caught insweet corn area was consist of 9 ordo, 23 family and 31 species and the lowest insect value intransgenic corn area was consist of 9 ordo, 22 family and 31 species. The highest relative frequencyvalue in sweet corn area was 11.4482 % and the lowest was 0.1718 %. The highest relativefrequency value in transgenic corn area was 18.6597 % and the lowest was 0.0343 %. The highestaccuraty relative value in sweet corn area was 4.2858 % and the lowest was 1.4286 %. The highestaccuraty relative value in transgenic corn area was 3.9473 % and the lowest was 1.3157 %.Shanon-Weiner (H’) Index varieties value of insect highest in sweet corn area is 2.8995 (medium),and in the transgenic corn area was 2.6455 (medium).Keywords : biodiversity. Arthropoda. transgenic Corn